Modern Solutions of Open Heart Surgery - Ahrorov Muhammad Aslamjonovich Asadov Behzod Burxon oʻgʻli Baxtiyorov Shoxrux Toir oʻgʻli Suvonov Shahzod Ergash oʻgʻli (Journal of Science in Medicine and Life, 2024)
Coronary artery disease (CHD) is a disease caused by partial or complete cessation of blood flow due to narrowing or blockage of the arteries, called "coronary arteries", that supply the heart muscle. Ischemic heart disease is the main cause of death in our country. About 200,000 people die from cardiovascular diseases in our country every year. The fatal feature of this disease is that it can lead to a life-threatening myocardial infarction in the later stages.